Experimental results on the irradiation of nuclear fusion relevant materials at the dense plasma focus 'Bora' device. (29th May 2015) - Cicuttin, A.; Crespo, M.L.; Gribkov, V.A.; Niemela, J.; Tuniz, C.; Zanolli, C.; Chernyshova, M.; Demina, E.V.; Latyshev, S.V.; Pimenov, V.N.; Talab, A.A.
Abstract: Samples of materials counted as perspective ones for use in the first-wall and construction elements in nuclear fusion reactors (FRs) with magnetic and inertial plasma confinement (W, Ti, Al, low-activated ferritic steel 'Eurofer' and some alloys) were irradiated in the dense plasma focus (DPF) device 'Bora' having a bank energy of ⩽5 kJ. The device generates hot dense ( T ∼ 1 keV, n ∼ 10 19 cm −3 ) deuterium plasma, powerful plasma streams ( v ∼ 3 × 10 7 cm s −1 ) and fast ( E ∼ 0.1 … 1.0 MeV) deuterons of power flux densities q up to 10 10 and 10 12 W cm −2 correspondingly. 'Damage factor' F = q × τ 0.5 ensures an opportunity to simulate radiation loads (predictable for both reactors types) by the plasma/ion streams, which have the same nature and namely those parameters as expected in the FR modules. Before and after irradiation we provided investigations of our samples by means of a number of analytical techniques. Among them we used optical and scanning electron microscopy to understand character and parameters of damageability of the surface layers of the samples. Atomic force microscopy was applied to measure roughness of the surface after irradiation. These characteristics are quite important for understanding mechanisms and values of dust production in FR that may relate to tritium retention and emergency situations in FR facilities. We also applied two new techniques. For the surface we elaborated the portable x-ray diffractometer that combines x-ray single photon detection with high spectroscopic and angular resolutions. For bulk damageability investigations we applied an x-ray microCT system where x-rays were produced by a Hamamatsu microfocus source (150 kV, 500 µ A, 5 µ m minimum focal spot size). The detector was a Hamamatsu CMOS flat panel coupled to a fibre optic plate under the GOS scintillator. The reconstruction of three-dimensional data was run with Cobra 7.4 and DIGIX CT software while VG Studio Max 2.1, and Amira 5.3 were used for segmentation and rendering. We have also provided numerical simulation of the fast ion beam action. The paper contains results on the investigations of modifications of the elemental contents, structure and properties of the materials.